1990
DOI: 10.1038/343461a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neurite polarity by tau antisense oligonucleotides in primary cerebellar neurons

Abstract: Neurons in culture can have fundamentally distinct morphologies which permit their cytological identification and the recognition of their neurites as axons or dendrites. Microtubules may have a role in determining morphology by the selective stabilization of spatially distinct microtubule subsets. The plasticity of a neurite correlates inversely with the stability of its component microtubules: microtubules in growth cones are very dynamic, and in initial neurites there is continuous incorporation of labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
378
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 615 publications
(392 citation statements)
references
References 13 publications
11
378
0
1
Order By: Relevance
“…Tau protein is crucial for the establishment of neuronal polarity during embryonic development, for axonal transport, and for the intracellular trafficking of various molecules (Caceres & Kosik, 1990; Dawson et al , 2001; de Barreda et al , 2010; Hernandez & Avila, 2010; Llorens‐Martin et al , 2011; Sapir et al , 2012). Given the tight control of Tau expression during AHN, it is reasonable to assume that this protein plays a regulatory role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Tau protein is crucial for the establishment of neuronal polarity during embryonic development, for axonal transport, and for the intracellular trafficking of various molecules (Caceres & Kosik, 1990; Dawson et al , 2001; de Barreda et al , 2010; Hernandez & Avila, 2010; Llorens‐Martin et al , 2011; Sapir et al , 2012). Given the tight control of Tau expression during AHN, it is reasonable to assume that this protein plays a regulatory role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether this phenomenon reflected a retraction of previously formed axons or an impairment in axon development, the neurite outgrowth response of cultured neurons from WT and mutant animals was quantitated at different time points after plating. For this analysis, an axon-like neurite was defined as a process at least twice as long as any other neurite of the same cell, and with a minimum length of 50 m (Dotti et al, 1998;Cáceres and Kosik, 1990). The results obtained clearly revealed that neurons from MAP1B mutant mice have a selective and significant inhibition of axon formation, a phenomenon that is likely to reflect a delay in axon outgrowth and also a reduced rate of elongation (Figure 2,.…”
Section: Delayed Axonal Formation and Growth Cone Abnormalities In Cumentioning
confidence: 97%
“…This is a prerequisite to establishing neuronal polarity and axonal outgrowth. 5,6 In addition, microtubules serve as tracks for the transport of cellular cargoes (vesicles, organelles) along axons and dendrites. 7 Both the dynamics and transport properties of microtubules are regulated by MAPs, such as tau.…”
Section: Cell Biology and Function Of Taumentioning
confidence: 99%